2017
DOI: 10.1128/aem.01820-17
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Localization of Sulfide:Quinone Oxidoreductase and Persulfide Dioxygenase of Cupriavidus pinatubonensis JMP134

Abstract: Heterotrophic bacteria have recently been reported to oxidize sulfide to sulfite and thiosulfate by using sulfide:quinone oxidoreductase (SQR) and persulfide dioxygenase (PDO). In chemolithotrophic bacteria, both SQR and PDO have been reported to function in the periplasmic space, with SQR as a peripheral membrane protein whose C terminus inserts into the cytoplasmic membrane and PDO as a soluble protein. JMP134, best known for its ability to degrade 2,4-dichlorophenoxyacetic acid and other aromatic pollutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…(ValdĂ©s et al, 2008a; Quatrini et al, 2009; Mangold et al, 2011; Chen et al, 2012; Yin et al, 2014; Christel et al, 2016). Similar localization of SQR was reported for Rhodobacter capsulatus (Schutz et al, 1999), while results for heterotrophic Cupriavidus pinatubonensis indicated that SQR located on the cytoplasmic side of the membrane and the soluble cytoplasmic PDO was in the vicinity of the membrane (Gao et al, 2017). The close location of SQR and PDO in the cytoplasm increases the efficiency of sulfide oxidation in heterotrophic bacteria (Gao et al, 2017).…”
Section: Sulfur Oxidation Network In Acidithiobacillus Sppsupporting
confidence: 71%
“…(ValdĂ©s et al, 2008a; Quatrini et al, 2009; Mangold et al, 2011; Chen et al, 2012; Yin et al, 2014; Christel et al, 2016). Similar localization of SQR was reported for Rhodobacter capsulatus (Schutz et al, 1999), while results for heterotrophic Cupriavidus pinatubonensis indicated that SQR located on the cytoplasmic side of the membrane and the soluble cytoplasmic PDO was in the vicinity of the membrane (Gao et al, 2017). The close location of SQR and PDO in the cytoplasm increases the efficiency of sulfide oxidation in heterotrophic bacteria (Gao et al, 2017).…”
Section: Sulfur Oxidation Network In Acidithiobacillus Sppsupporting
confidence: 71%
“…The activity of SQR Cp relies on the electron transport chain in cell membrane [ 40 , 41 ], and the prepared crude membrane fraction was sufficient to detect SQR activity [ 42 ]. In order to maintain the SQR Cp activity as in native state, the membrane factions of SQR Cp or SQR Cp -C94S proteins overexpression cells were extracted to characterize the enzyme activity in all the biochemical assay in vitro.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfides (S 2− , HS − , and H 2 S) are widely distributed in soils, ore, wastewater, and marine environments. They are produced partly from mineral deposits, and partly by biological metabolism, including as products of eukaryotic and prokaryotic endogenous catabolism of cysteine and iron–sulfur proteins and dissimilatory metabolism of sulfur-containing inorganic compounds ( Kabil and Banerjee, 2010 ; Lencina et al, 2013 ; Gao et al, 2017 ; BeƂtowski, 2019 ). H 2 S is an important electron donor in prokaryotes, such as phototrophic or chemotrophic microorganisms ( Reinartz et al, 1998 ; Sakurai et al, 2010 ; Klatt et al, 2015 ).…”
Section: Sulfur Metabolism In the Order Sulfolobalesmentioning
confidence: 99%